Mobile Application Reminder Of SPP Payment Schedule's And School Activities Information Based SMS Gateway - Sari, Febrina; Lidya, Putri (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
The purpose of this research is to build information facilities of SPP Payment Schedule and Dissemination of Information Activities at Alfaduta Dumai kindergarten. This application is able to handle the payment process and convey information activities more efficiently using the information technology. This application will help to disseminate the information quickly and reduce the lateness of payment information by using SMS facility (Short Message Service) Gateway to parents/guardians. This application uses SMS Gateway that can disseminate the message to users automatically and quickly. It is directly connected to the database of mobile phone numbers and the operator does not have to type in hundreds of numbers and messages on the mobile phone, as all the numbers will be taken automatically from the database. This mechanism allows all kinds of announcements to be sent via SMS using Mobile Application Reminder Payment Schedule SPP and School Activities Information. The SMS Gateway will be able to facilitate the administrator and the school to provide various information to parents or guardians, and overcome the lateness of SPP payment every month.